A Novel Inward Gradient Self-Lubrication Layer with Soft Alloys and Its Lubricating Mechanism - Songshan Yan; Ling Qin; Rui Hu; Zuomin Liu (Advances in Materials Science and Engineering)
A novel ceramic composite inward gradient distribution layer has been developed. The layer is a lubricating layer in which soft-metal lubricants are compounded into the ceramic matrix by high frequency induction infiltrating method. The design of the layer and its lubricating mechanism are investigated in the paper. The results show that the property of the layer greatly depends on the wetting angle of the soft-metal lubricants on the matrix and the proportion of Ag, Cu, Sn, and Pb as well as the infiltrating parameters. Based on a lot of experiments, a novel inward gradient layer with Pb28Sn19Ag6Cu has been developed. The layer has an excellent lubricating property (friction coefficient about 0.2~0.3 at 600°C). The research reveals the lubricating mechanism, observing the phenomenon that the soft-metal in the matrix diffuses out of the frictional surface, and measures the lubricating film thickness as about 20 μm on the worn surface.